2006
DOI: 10.1110/ps.052004006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of protein aggregation by polyethylene glycol conjugation: GCSF as a case study

Abstract: Polyethylene glycol (PEG) conjugation to proteins has emerged as an important technology to produce drug molecules with sustained duration in the body. However, the implications of PEG conjugation to protein aggregation have not been well understood. In this study, conducted under physiological pH and temperature, N-terminal attachment of a 20 kDa PEG moiety to GCSF had the ability to (1) prevent protein precipitation by rendering the aggregates soluble, and (2) slow the rate of aggregation relative to GCSF. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 48 publications
5
85
1
Order By: Relevance
“…For example, the steric hindrance of the glycan moiety in glycosylated proteins and polyethylene glycol (PEG) in the pegylated proteins was suggested to play an important role in stabilizing their linked proteins against aggregation. 39,40 The steric hindrance appears to be highly reasonable because protein aggregation is a specific and multimolecular assembly process. It was recently shown that the folded N-terminal domains, by acting solubility enhancer, have the potential to assist de novo folding of their downstream domains in vivo, contributing to an autonomous folding of multidomain proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the steric hindrance of the glycan moiety in glycosylated proteins and polyethylene glycol (PEG) in the pegylated proteins was suggested to play an important role in stabilizing their linked proteins against aggregation. 39,40 The steric hindrance appears to be highly reasonable because protein aggregation is a specific and multimolecular assembly process. It was recently shown that the folded N-terminal domains, by acting solubility enhancer, have the potential to assist de novo folding of their downstream domains in vivo, contributing to an autonomous folding of multidomain proteins.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF, a 20 kDa four-helix bundle protein, is a cytokine that regulates differentiation of hematopoietic progenitor cells towards mature neutrophils. 44 The G-CSF protein drug filgrastim, marketed by Amgen under the registered trade name Neupogen s , is produced by recombinant methods, and used in chemotherapy. Unfortunately, the tendency of G-CSF to aggregate at moderate concentrations and physiological conditions compromises its therapeutic benefit.…”
Section: Pegylated Proteinsmentioning
confidence: 99%
“…45,46 Thus, the success of PEGylated G-CSF appears to be due to a combination of preventing gross protein aggregation, which can cause adverse reactions during therapeutic treatments, and solubilizing the aggregated states that tend to form even after PEGylation. 44 While the benefits of PEGylation for increasing the efficacy, and reducing immunogenicity, of therapeutic proteins and small molecule drugs is proving fruitful, other polymer structures present intriguing alternatives. Phosphorylcholine (PC)-based polymers represent one interesting potential example of a PEG-replacement.…”
Section: Pegylated Proteinsmentioning
confidence: 99%
“…In order to overcome this problem, the polypeptide has been conjugated to an inert polyethylene glycol (PEG) molecule for improved bioavailability by prolonging the plasma serum half-life of proteins with increasing their hydrodynamic volume which leads to a decrease in its renal clearance (Abuchowski et al, 1984;Bailon & Berthold, 1998;Harris & Chess, 2003;Pasut & Veronese, 2007). Additionally, the conjugation (covalent attachment) (Freitas et al, 2010;Rajan et al, 2006) of the polypeptide to PEG has several other advantages such as improved stability, increased solubility, reduced enzymatic degradation, immunogenicity, and toxicity of the conjugated protein (Abuchowski et al, 1984;Freitas et al, 2010;Harris & Chess, 2003;Pasut & Veronese, 2007;Rajan et al, 2006;Wang et al, 2010). As a result, the number of commercially available PEGylated G-CSF variations for human applications utilizing these advantages has increased significantly in the last few years.…”
Section: Introductionmentioning
confidence: 99%